Life Skills and Experiential Learning on Work-Based Learning (Case of Travel Business Students) - Aini, Windra (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2021)
This study aims to analyze the learning experience gained by students of the Travel Business while doing internships in the Travel Bureau industry. The research method used is quantitative descriptive. This study resulted in three important findings: 1) Students at WBL were not given enough trust to make reservations, booking, and printing; 2) The experience of doing ticketing and printing cannot be given by all industries because not all Travel Agencies act as agents; 3) Dominant students during the WBL are given the trust to use office work facilities and communicate with customers.